Simultaneous Determination of 16-Hydroxystrychnine and Demethylbrucine by LC-MS/MS in Rat Urine and Its Application to Pharmacokinetic Study - Yan, Rui; Xia, Bin; Zhang, Shan (Drug Metabolism and Bioanalysis Letters, 2023)
Introduction: This paper aimed to establish a method to help investigate the combination mechanism of traditional Chinese medicine from the metabolic perspective. Background: Semen Strychni has been a frequently used herb in clinics for a long time. In traditional Chinese medical science, Semen Strychni always combinate with other herbs to modulate its nature of severe toxicity. However, the mechanism of the combination is still unclear. Previous research mostly focused on the components of the herbs. The metabolic processes of the main components of the Semen Strychni are also very important and have rarely been reported. Objective: This study tended to develop a rapid and sensitive high-performance liquid chromatographic- tandem mass spectrometric (HPLC-MS/MS) method for the determination of two major metabolites of Semen Strychni in rat urine. Methods: Chromatographic separation was carried out on a C18 column. Detection was performed by a selective reaction monitoring (SRM) mode via an electrospray ionization (ESI) source operating in the positive ionization mode. Analysis of analytes from rat plasma was carried out by protein precipitation using acetonitrile. Results: The assay was validated in terms of specificity, precision, recovery, etc. The intra- and inter-day precision values were less than 13.1%. The recoveries at three levels were more than 69.1%. The method was then used to study the kinetic profiles of the metabolites of Semen Strychni in rat urine for the first time. Conclusion: The results demonstrate that the established LC/MS method in this study is accurate and sensitive for the simultaneous determination of the two metabolites of Semen Strychni in rats' urine samples. This method could be a supplement to the plasma pharmacokinetics of Semen Strychni.
Keywords: LC-MS/MS